Hubungan Perhatian Orang Tua terhadap Hasil Belajar Peserta Didik pada Pembelajaran Geografi - Khalijah, Siti; Suprapta, Suprapta; Abbas, Ibrahim (UNIVERSITAS NEGERI MAKASSAR, 2021)
This study aims to determine: 1). Knowing how the level of parental attention to the learning outcomes of students in the Social Studies class of SMA Negeri 3 Makassar. 2) Knowing whether there is a significant relationship between parental attention and geography learning outcomes of class X IPS SMA Negeri 3 Makassar. This research is an ex post facto research with a correlational approach. The independent variable in this study is the attention of parents while the dependent variable is learning outcomes. The sampling technique used was random sampling, the number of samples was 52. The data collection was obtained using a questionnaire containing questions about students' attention to learning and learning outcomes, namely the first semester scores with school documentation. The data analysis technique used is descriptive statistics and product moment correlation analysis. The results shssowed that the level of people's attention was categorized as moderate, namely 78 with a percentage of 65%, while the results of learning geography for class X IPS students at SMA Negeri 3 Makassar were categorized as moderate, namely 80 with a percentage of 80%. The results of the product moment correlation analysis obtained = 0.567 and = 0.230 with an error rate of 5% (0.05). It can be concluded that parental attention has a significant effect on student outcomes in geography learning.